Knowledge difference of sexually transmitted infections between Hong Kong undergraduates from local and international secondary schools: A cross-sectional study - Wong, Darren Li Liang; Zhang, Allen; Cheung, Kylie K. Y.; Choi, Edmond Pui Hang; Lam, May P. S. (Frontiers in Public Health, 2022)
Background Since the delivery of sex education is not standardized across local and international secondary schools in Hong Kong, this study aims to assess and compare the knowledge level of sexually transmitted infections (STIs) between university students who attended local and international secondary schools in Hong Kong. Methods From January to March 2019, we conducted a cross-sectional survey among undergraduates at the University of Hong Kong. The primary outcome was STI knowledge as measured by a 29-item quiz. A higher quiz score meant a better STI knowledge level. Students' attitude toward sexual health and their sex education history was collected. Bivariate and multivariate analyses were conducted to evaluate the association factor with a better STI knowledge level. Results Three hundred and ninety six students were included in the analysis. Three hundred thirty three (85.35%) students attended local secondary schools and 58 (14.65%) students attended international secondary schools in Hong Kong; 200 (50.51%) students were male and 196 (49.49%) students were female. Compared with students from local secondary school, those from international secondary schools had a significantly higher STI quiz score (18.19 vs. 15.4, p = 0.003). The results of multiple linear regression revealed that students in a higher year of study (β = 1.07, p < 0.001), from medical faculties (β = 6.96, p < 0.001), and from international secondary schools (β = 2.27, p = 0.003) achieved a higher STI quiz score. Conclusion University students who attended international secondary schools in Hong Kong possess a significantly higher knowledge level of STIs compared with those who attended local secondary schools. Nonetheless, the overall STI awareness among university students is inadequate. The inadequacy of STI awareness calls for the need to plan and implement satisfactory, comprehensive, and standardized sex education across the overall education system in Hong Kong.